Effect of herbal mouthwash on periodontal parameters and P. gingivalis - Sonam Mufti (Advances in Human Biology, 2017)
Introduction: Inadequate control of dental plaque is one of the primary causative factors in the development of gingivitis and periodontal disease progression. Numerous agents have been available to reduce this plaque. Studies have shown the effects of chlorhexidine (CHX) and herbal mouthwash (HM) individually, but limited evidence has compared the efficacy of both clinically and microbiologically. Hence, this study evaluated the efficacy of HM and CHX on Porphyromonas gingivalis along with that of clinical parameters. Materials and Methods: This study was a randomised controlled double-blinded study. Thirty participants were divided into two groups (15 test and 15 controls). Each participant had undergone scaling and root planing and was then given either of the mouthwashes. Oral hygiene index-simplified, plaque index, gingival index and bleeding on probing were recorded. Subgingival plaque samples were taken to evaluate P. gingivalis by polymerised chain reaction. Results: HM showed significant results, and when antimicrobial efficacy was combined, clinically no statistical significance was seen compared to CHX. Participants' perception was also similar for both mouthwashes. Conclusion: HM was found equally effective against periopathogens and well accepted by the participants.